The Use of mono cylinder in decreasing level of dust - Hari Rudijanto Indro Wardono; Tri Cahyono; Zaeni Budiono (Poltekkes Kemenkes Semarang, 2014)
This research is quacy experiment with 2 factorial design used Random Complete Block Design, which made only limited where each treatments has the same intensity or dose. The number of samples is 108 samples. Data analysis using One Way Anova and LSD. It can be concluded that mono cylinder 100 cm high can reduce dust levels on average 56.21%, mono cylinder 75 cm average 35.41% and mono-cylinder 50 cm average 33.53%. Structure ARSPSE (Active Charcoal-Spon-Coconut fibers) can reduce levels of dust for average - 46.51%. One Way ANOVA test showed there were significant differences reduction in dust levels with varying heights mono cylinder (sig 0.015 less than 0.05). The resut suggested that the perpetrators of domestic industries using flue mono-cylinder combustion process and for further research can be modified tools ,materials and used water resirculation system as well as gas and to decrease air pollutants such as SOx, HC.